The concept of joyful foods according to the islamic perspectives / Mohamad Hasif Jaafar ... [et al.] - Jaafar, Mohamad Hasif; Satari, Hisam; Mat Salleh, Mohd Kamel; Hassannudin, Mohamad Iadid Ashrai (Universiti Teknologi MARA, Perak, 2023)
Food not only affects the physical body, but also the brain. Eating can bring about a range of emotions, such as joy and frustration, and can play a role in mental health. Studies have shown that certain foods can increase brain chemicals like dopamine and norepinephrine, which can improve mood, motivation, and concentration. Eating fruits and vegetables can also provide essential nutrients and improve mood by reducing anger and stress. Although the association between food and mood has been proven by several studies, there is limited literature regarding consumption of foods which can bring happiness and joy according to Islamic perspectives. In this research, we analyzed the practical relevance and significance of joyful foods based on Islamic viewpoints, emphasizing on gaining blessings and joy. Theories from prominent Islamic philosophers including Al-Ghazali, An-Nawawi, Al-Farabi, and Ibn Miskawayh were analyzed throughout the study.